Electronic, optical and thermoelectric properties of new metal-rich homological selenides with palladium–indium: Density functional theory and Boltzmann transport model. (March 2020) - Azam, Sikander; Goumri-Said, Souraya; Khan, Saleem Ayaz; Kanoun, Mohammed Benali
Abstract: We reported first principles calculations of electronic and related optical and thermoelectric properties of two metal-rich palladium–indium selenides Pd5 InSe and Pd8 In2 Se. Both selenides are found to be metallic and their densities of states at the Fermi energy, N (EF ), showed an overlap between the Pd- s/p, In -p and Se -p states. Specific heat coefficients were found 0.52 and 0.743 mJ/mol·K 2, for Pd5 InSe and Pd8 In2 Se, respectively. Our findings indicate that the linear optical properties have potential use as active photo-catalyst under visible light irradiation. We combined the Boltzmann transport equations with density functional theory to determine the thermoelectric and electrical properties of both compounds. At 300 K, the Seebeck coefficient of Pd8 In2 Se is larger than Pd5 InSe one. Due to their metallic character, both selenides have limited thermoelectric use in their current structures and could be doped to change their electronic structures to narrow semiconductors or semi-metallic materials. Graphical abstract: Image 1 Highlights: DFT calculations of electronic, optical and thermoelectric properties of Pd5 InSe and Pd8 In2 Se. Both selenides are found metallic. Linear optical properties have potential use as active photo-catalyst under visible light irradiation. Boltzmann transport model combined with DFT to determine the thermoelectric properties.